EDUCATION ON FALL PREVENTION AND BALANCE MAINTENANCE AMONG THE ELDERLY IN SEGERI DISTRICT, PANGKAJENE AND ISLANDS REGENCY - Nur Aulia Liwaulhamdiah; Nirmala Sri Damansi; Abhista Ibnu Fauzan; Fatoni Fatoni; St Zulaiha Nurhajarurahmah (Universitas 'Aisyiyah Bandung, 2026)
Falls are a common health issue among the elderly and can lead to injuries, reduced functional ability, dependency, and a decline in quality of life. The public’s lack of understanding regarding risk factors and preventive measures is one of the barriers to reducing fall incidents at the community level. This community service activity aims to improve public understanding of the importance of maintaining postural stability and taking preventive measures against falls. The activity was conducted in Segeri Subdistrict, Pangkajene and Islands Regency, targeting the general public, particularly the elderly. The methods used included initial assessments using the Fukuda Stepping Test and the Four Square Step Test, education, interactive discussions, and demonstrations of exercises that can be performed independently at home. Based on the results of the Fukuda Stepping Test, the majority of participants fell into the moderate-risk category, totaling 18 people (45%), while 11 people (27.5%) were in the low-risk category and 11 people (27.5%) were in the high-risk category. Based on the Four Square Step Test, the majority of participants were also in the moderate category (17 people, 42.5%), followed by the low category (12 people, 30%) and the high category (11 people, 27.5%). These findings indicate that most participants have a potential for stability issues requiring attention through promotive and preventive efforts. The activity proceeded smoothly and received positive feedback from the participants. This program is expected to raise public awareness of adopting active and safe lifestyles to support independence and quality of life in older adults.